BIOFERTILIZATION AND ITS ROLE IN SUSTAINABLE AGRICULTURE: A REVIEW - W. M. Al-Joboory (مجلة الأنبار للعلوم الزراعية, 2025)
The continuous use of chemical fertilizers has many adverse effects on the environment, such as soil degradation, groundwater pollution, shrinking biodiversity, and higher gas emissions. Although fertilizers increase the productivity of most crops, high concentrations of some elements in them may be injurious to health. Biofertilizers are one of the modern technologies for reducing excessive use of mineral fertilizers as they contribute significantly to improving the chemical, physical, and biological properties of soil, maintaining nutritional balance in agricultural soils, and converting them into forms ready to feed the plant. They are also less costly as they speed plant growth, in addition to secreting antibiotics that strengthen plant resistance to diseases and pests endemic to the soil and contribute to the secretion of various enzymes that stimulate plant growth. Therefore, biofertilizers are essential components of sustainable agriculture with positive long-term effects on soil fertility